The moderating role of resiliency on the negative effects of childhood abuse for adolescent girls involved in child welfare. (February 2017) - Tlapek, Sarah Myers; Auslander, Wendy; Edmond, Tonya; Gerke, Donald; Voth Schrag, Rachel; Threlfall, Jennifer
Abstract: Child abuse is associated with a number of negative psychosocial outcomes, including mental health problems, substance abuse, and interpersonal violence. Yet some children thrive or "adapt well" despite experiencing abuse; researchers are increasingly interested in the protective factors and mechanisms that may prevent negative outcomes. The purpose of this study was to explore the role of resiliency characteristics in the relationship between childhood abuse and the negative outcomes of depression, posttraumatic stress disorder (PTSD), substance abuse, and revictimization in adolescent girls involved in child welfare. Participants were 237 adolescent girls ages 12–19 years ( M = 14.9, SD = 1.6), and who were youths of color (75%) and white (25%). Data were collected through surveys assessing histories of physical, sexual, and emotional child abuse; symptoms of posttraumatic stress and depression; lifetime substance use; and experiences of physical, verbal, and relational revictimization in the last three months. All forms of childhood abuse were significantly associated with symptoms of depression and PTSD as well as revictimization and substance use. Higher levels of resiliency were associated with fewer depression and PTSD symptoms and experiencing less revictimization. Resiliency significantly moderated the relationship between sexual abuse and depression, PTSD, and revictimization. Resiliency also moderated the relationship between emotional abuse and depression. No significant interactions emerged in the relationship between physical abuse and any of the mental health and behavioral problems. This study suggests that resiliency may serve as a protective factor in the relationship between abuse (sexual and emotional) and depression, PTSD, and revictimization during adolescence. Highlights: High resiliency mitigated the negative effects of abuse on PTSD and depression. High resiliency mitigated the negative effects of sexual abuse on revictimization. Resiliency may be a protective factor for girls with histories of child abuse.